2014
DOI: 10.1017/s026646231400052x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Mobile Reporting Systems in Social Home Care: The Case of Seven Swedish Municipalities

Abstract: The mobile systems yield benefits for all the actors, that is, municipalities, care recipients and care providers. These enhance the public-private coordination and cooperation in social home care in Sweden. The municipalities are called upon to address change management and technical challenges in the implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In the group of barriers related to hardware and software, we found that users reported system malfunctions, poor design, and issues regarding software configuration. 35,40,46,63,66,67,70,71,85 In these studies, the software did not reflect users' needs and expectations or did not support their information needs. 70 Some studies described the lack of documentation features.…”
Section: Barriersmentioning
confidence: 98%
See 4 more Smart Citations
“…In the group of barriers related to hardware and software, we found that users reported system malfunctions, poor design, and issues regarding software configuration. 35,40,46,63,66,67,70,71,85 In these studies, the software did not reflect users' needs and expectations or did not support their information needs. 70 Some studies described the lack of documentation features.…”
Section: Barriersmentioning
confidence: 98%
“…We classified the selected studies in five groups, according to the main purpose of ICT use by health care aides: (1) improve everyday work (n ¼ 12, 30%), 46,[51][52][53][54][55][56][57][58][59][60][61] (2) access electronic health records for home care (n ¼ 9, 22.5%), [62][63][64][65][66][67][68][69][70] (3) facilitate client assessment and care planning (n ¼ 9, 22.5%), [71][72][73][74][75][76][77][78][79] (4) enhance communication (n ¼ 7, 17.5%), 2,40,80-83 and (5) provide care remotely (n ¼ 3, 7.5%). 35,84,85 Fig.…”
Section: Study Purposementioning
confidence: 99%
See 3 more Smart Citations